RATIONALIZATION AND INVENTION AS A MEANS OF IMPLEMENTING A RESTORING PROGRAM IN UKRAINE (1943–1950) - Vetrov І. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
The article deals with a complex of issues related to the implementation of rehabilitation policy in the field of Ukraine’s heavy industry at the final stage of the Second World War and post-war years. The approaches of the state leadership to the development of rationalization and invention, departmental scientific research, as an instrument for the intensification of production, optimization and improvement of the organization and labor methods in the conditions of a total shortage of skilled labor, material and technical and financial resources, the invention and testing of new methods of organization of labor, technical devices , mechanisms, improvement of technologies not only gave a tangible economic effect, but also contributed to the modernization of production. Party and trade union bodies in every way stimulated and propagated the movement of innovators and inventors both moral and material resources. In a directive form, the heads of industrial enterprises were obliged to develop rationalization and invention and to report regularly on the results of this work. The movement of rationalizers and inventors allowed many workers, technicians, engineers to identify their abilities, which contributed to the increase of social status and recognition, as well as the material gain in the form of bonuses and other rewards. In addition, he motivated the workers and the ITP to improve their educational and professional level. At the same time, many innovative proposals and inventions have overcome the difficult path of introduction into production due to lack of funds and necessary materials, equipment, aggregates. Yet, in the absence of foreign know-how, inventors and innovators largely offset this deficit, which positively influenced the pace of reconstruction of Ukraine’s industrial potential.